SHIA COMMUNITY (A RESEARCH EVERYDAY LIVES OF THE SHIA COMMUNITY IN SALATIGA, CENTRAL JAVA) - Retnowati, Retnowati; Efriadi, Yedi (Analisa: Journal of Social Science and Religion, 2016)
This research seeks to explain the existence of Shia community at Pancuran village, in  Salatiga, Central Java, Indonesa, and how their strategies to survive in the midst society in that region. To obtain data on the Shia community at Pancuran, Salatiga, it was done through in-depth interviews, and observations are preceded by a close observation prior to the study. This research also examines some relevant literatures and documents to the research problem as the secondary data. The theory of religious freedom and cultural identity of religious pluralism in the Shia community are used to describe and to analyze the problem of research based on the obtained data. The results show that the Shia community in Salatiga is not discriminated, and they can live in Salatiga freely along with other religious communities and Salatiga society at large. This is supported by an inclusive attitude among Shia community and society Salatiga in building relationships and communication with people of other faiths. Local knowledge possessed by people of Salatiga can be a social capital for implementing inter-religious harmony.